A Semiotic Analysis of Djarum 76 Television Advertisements - Insan Fadilah Fulki (Universitas Pendidikan Indonesia (UPI), 2013)
This research is geared towards discovering the representation of corruption in Djarum 76 television advertisements “Kontes Jin” and “Pungli” versions and revealing the ideology behind the advertisements. The research utilizes descriptive qualitative method. Drawing on data in the form of videos, the transformed scenes were analyzed using Selby Coedery’s(1995) theory of visual elements of television advertisement, and Barthes’(1977)theory of orders of signification. The research reveals that corruption in the advertisements is represented as a terrifying problem in Indonesia and is difficult to annihilate. Corruption is also represented as the product of materialism, which appears when the excessive desire of collecting affluence is not fulfilled. The research also reveals that materialism and corruption culture are the ideologies which can be found in the advertisements. Keywords: Representation, Ideology, Corruption, Djarum 76